Hubungan Karakteritik, Sumber Informasi dan Dukungan Keluarga dengan Persepsi Penerimaan Vaksinasi COVID-19 pada Mahasiswa - Erna Sariana; Rosidawati Rosidawati (Universitas Faletehan, 2023)
COVID-19 vaccination is an effort to deal with COVID-19 pandemic. People’s good perception of vaccine acceptance contributes to the achievement of vaccination. The purpose of the study was to determine the relationship between characteristics, sources of information, and family support with students’ perceptions of acceptance of COVID-19 vaccination. The research design was cross-sectional. The samples were 67 students of first to third year at Diploma IV Physiotherapy Study Program of Poltekkes Kemenkes Jakarta III. The data analysis was univariate, bivariate (chi-square test), and multivariate (logistic regression test). The results of the study showed that most of the respondents had a good perception of vaccine acceptance (50.8%), were <21 years (76.9%), female (87.7%), lower semester level (78.5%), had a family health history of COVID-19 (53.8%), good sources of information (50.8%), and lack of family support (50.8%). There was a significant relationship between the perception of COVID-19 vaccination acceptance, age (p = 0.022 and OR = 5.524), family health history of COVID-19 (p = 0.004 and OR = 5.091), source of information (p = 0.004 and OR = 5.060), and family support (p = 0.0001 and OR = 8.000). The highest dominant factor was the source of information (OR = 15.340). Sources of information, such as mass media, friends, and society, can influence individuals’ learning process, leading to the acquisition of knowledge and eventually affecting their perception and behaviors.